PENGARUH PEMBERIAN PUPUK KOMPOS SEKAM PADI DENGAN BERBAGAI BIOSTARTER TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) - Ni Made Nitarini; Mihwan Sataral (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2022)
Lack of nutrient availability in the soil is one of the factors affecting melon plant production, so this study aims to determine the best effect and type of compost with various biostarters on the growth and yield of melon plants. This research was carried out on agricultural land in Bumi Beringin Village, North Luwuk District, Banggai Regency, this research was carried out in June 2021. This research used a randomized block design (RAK) method which consisted of 1 factor with 3 replications and consisted of 5 treatments so that there were 15 experimental units. The results showed that observing the growth and yield of melon plants, it could be concluded that (1) the treatment of rice husk compost had a very significant effect on the observed variables of plant length at 3, 4 and 5 weeks WAP with the best results in treatment P1 (compost rice husk with EM4 biostarter 640 g/hole) with an average of 18.78, 42.34 and 57.13 cm. (2) Application of rice husk compost fertilizer with EM4 biostarter had a significant effect on the variable number of fruit plantations with an average of 3.11.